2022
DOI: 10.1039/d2nj02770d
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of porous graphitic carbon nitride with N3C nitrogen vacancies by a CaCO3 template for improved photocatalytic H2 evolution

Abstract: Porous graphitic carbon nitride with nitrogen vacancy (N-CN) has been successfully synthesized by a facile CaCO3 template method. The porous structure contributed to increased surface area of obtained N-CN photocatalyst....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Certain instances, electron rich environment was observed and caused the shielding effect after the introduction of N-related defects in melem motifs. [48,77,102] Besides these traditional peaks, C i and C e , new peaks appeared and associated with electron withdrawing substituents such as cyano, [92,111,129] amide, [65] etc. [98] (Figure 5d).…”
Section: Unraveling the N-vacancy Puzzle: Synthesis Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain instances, electron rich environment was observed and caused the shielding effect after the introduction of N-related defects in melem motifs. [48,77,102] Besides these traditional peaks, C i and C e , new peaks appeared and associated with electron withdrawing substituents such as cyano, [92,111,129] amide, [65] etc. [98] (Figure 5d).…”
Section: Unraveling the N-vacancy Puzzle: Synthesis Strategiesmentioning
confidence: 99%
“… [99,100] While theoretical calculations indicate that removing NH x requires less energy compared to N 2C , the majority of studies have consistently reported the preferential loss of N 2C [101] . Certain reaction conditions, like the previous one, [64] using CaCO 3 template, [102] calcination in the presence of air [75] and the use of HNO 3 , [83] resulted in the removal of N 3C lattice sites. Many strategies alike replacing N atom with an element (P, O and S) or inducing vacancy in the presence of other dopants (Se, Mn, Cu and Mg) contributed to the determination of missing N atom and the location of these atoms by comparing the binding energy changes in XPS [69,103–108] …”
Section: Unlocking N‐vacancies In Cn: Characterization Techniquesmentioning
confidence: 99%